Perancangan Model Bisnis Outlet Ritel Modern dengan Menggunakan Metode IDEF0 dari Perspektif Retailer Value Chain - Sugiarto, Emaria; Ramadhanti, Lifia Citra; Putra, Fibi Eko (JURNAL TEKNIK INDUSTRI, 2021)
The development of the retail business in Indonesia has encouraged the rise of modern grocery stores. Competition in this business is intensifying, which prompts every retailer to further improve the systems and technologies used in running their business to improve the value chain. One of them is by applying a clear business process model as a reference in conducting daily business activities. Various business process modeling techniques have been applied in several businesses. One of the modeling techniques that can be used for retail business is the IDEF0 method. The method is capable of identifying the flow and sequence of processes in a retail business. After getting a clear business model, then make the development (become a model) of the existing business model (as is model) to be able to further improve business performance. In this study, the supermarket business process model that has been implemented has been identified, the business model has been developed into a new model for analysis then the comparison between the as is model and the to be model. The goal is to measure the improvement in the performance (value chain) of the development carried out. Research shows the performance of stock on hand (SOH) is increasing and the level of depletion of stock (OOS) is decreasing in supermarkets.